Outcome of Concurrent Occult Hemothorax and Pneumothorax in Trauma Patients Who Required Assisted Ventilation - Ismail Mahmood; Zainab Tawfeek; Ayman El-Menyar; Ahmad Zarour; Ibrahim Afifi; Suresh Kumar; Ruben Peralta; Rifat Latifi; Hassan Al-Thani (Emergency Medicine International)
Background. The management and outcomes of occult hemopneumothorax in blunt trauma patients who required mechanical ventilation are not well studied. We aimed to study patients with occult hemopneumothorax on mechanical ventilation who could be carefully managed without tube thoracostomy. Methods. Chest trauma patients with occult hemopneumothorax who were on mechanical ventilation were prospectively evaluated. The presence of hemopneumothorax was confirmed by CT scanning. Hospital length of stay, complications, and outcome were recorded. Results. A total of 56 chest trauma patients with occult hemopneumothorax who were on ventilatory support were included with a mean age of 36 ± 13 years. Hemopneumothorax was managed conservatively in 72% cases and 28% underwent tube thoracostomy as indicated. 29% of patients developed pneumonia, 16% had Acute Respiratory Distress Syndrome (ARDS), and 7% died. Thickness of hemothorax, duration of mechanical ventilation, and development of ARDS were significantly associated with tube thoracostomy in comparison to no-chest tube group. Conclusions. The majority of occult hemopneumothorax can be carefully managed without tube thoracostomy in patients who required positive pressure ventilation. Tube thoracotomy could be restricted to those who had evidence of increase in the size of the hemothorax or pneumothorax on follow-up chest radiographs or developed respiratory compromise.